Gen Z Strategy in Civic Education Learning for Character Education Implementation - Kamelia, Siera Aufa (International Journal of Students Education, 2024)
Generation Z has unique characteristics in learning, which requires special strategies to implement character education in Citizenship Education (PKn) subjects. Digital technology, social media, and project-based learning methods are considered effective in meeting their learning needs based on interaction and contextual relevance. This study aims to explore appropriate learning strategies for Generation Z in PKn to develop character values. The method used is a literature review with a descriptive analysis approach. Data were obtained from various literatures, such as national and international journals related to learning strategies for Gen Z, character education, and the use of technology in PKn. The results of the study show that the use of social media and digital technology in PKn learning provides space for students to interact more actively and flexibly, so that citizenship values can be better understood. Project-based learning allows students to apply character values in real contexts through social activities, such as anti-bullying campaigns or environmental projects. In addition, digital interaction through online discussions plays a role in developing character values such as tolerance and a sense of responsibility. With this interactive and contextual approach, Gen Z can more easily internalize character values, which are relevant to facing social challenges in the digital era.